Дочки-матери на выживание: [роман] / Юлия Лавряшина - Лавряшина Юлия Александровна (Э, 2017)
Экземпляры: СБ (20180416) / Инвентарный номер: 55938 / Цена: 222.94 / Сис.шифр: Р2 / Авт.знак: Л13 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6